Fenomena LGBTQ dan faktor-faktor yang meningkatkan penglibatan masa kini [LGBTQ phenomena and factors increasing involvement today] - Zaifuddin Md Rasip; Anis malik toha; Mohd Solleh Ab Razak; Siti Aisyah Yap binti Abdullah (Persatuan Sains Sosial dan Kemanusiaan Muallim, 2025)
The LGBTQ population is growing in size, and this phenomenon is drawing attention from all around the world. They are also growing increasingly outspoken in their demands for legal rights and social acceptance. But along with increased awareness come worries about health problems, especially the rising HIV prevalence in the community. The purpose of this study is to investigate the LGBTQ phenomena utilising a qualitative methodology and library research techniques. This method makes it possible to comprehend the problems this society faces on a deeper level from a variety of angles, including social, psychological, health, and religious ones. The main objective of the study is to identify the factors that drive increased involvement in the LGBTQ community. The study identifies numerous significant aspects through a literature review that includes a variety of perspectives and ideas, including social environment influences, stigma, the search for selfidentity, and the need for emotional support. The findings are expected to provide valuable insights for building more effective preventative and support programs for LGBTQ people, assisting them in navigating their recovery process and improving their overall well-being. Understanding these reasons allows us to take proactive actions to change the situation and provide the necessary assistance for those in the LGBTQ community to better their situations and return to their true selves. This study is intended to promote awareness and establish a more inclusive space for conversation in society, as well as to assist future researchers in constructing more appropriate and thorough recovery modules.